The charismatic theology of St. Luke - Stronstad, Roger (Peabody, Massa.. Hendrickson Publishers, 2005)
"The meaning of this book is that the walls must come down between Pentecostals and evangelicals. If canonical Luke has a charismatic theology as Stronstad proves, we cannot consider Pentecostalism to be a kind of aberration born of experiential excesses buta 20th century revival of New Testament theology and religion. It has not only restored joy and power to the church but a clearer reading of the Bible as well." --
The Holy Spirit in Luke-Acts : a challenge in methodology -- Prolegomenon : the charismatic Spirit of God -- The Holy Spirit in the Gospel of Luke : the charismatic Christ -- The Holy Spirit at Pentecost : the charismatic community -- The Holy Spirit in the Acts of the apostles : the charismatic community in mission -- The charismatic theology of St. Luke : synthesis and challenge.
Revision of the author's thesis (master's)--Regent College, 1975.
Includes bibliographical references (pages 85-91) and index.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Holy Spirit -- Biblical teaching; Gifts, Spiritual -- Biblical teaching; Glossolalia -- Biblical teaching